An Innovative Network to Improve Sea Ice Prediction in a Changing Arctic - Bitz, Cecilia M (2014)
The overarching goal of this project is to understand sea ice predictability and improve sea ice predictions system by defining key observations, improve technical approaches for prediction, and refine communication of predictions.